Self Care, Personality Traits, and Burnout in Emergency Nurses - Imardiani Imardiani; Efroliza Efroliza; Ella Rusnida (Media Keperawatan Indonesia, 2022)
Emergency nurses are health professionals who are very susceptible to burnout. There are many factors that influence nurses' burnout levels, including self-care and personality traits, but the relationship between burnout is still unclear. The purpose of the study was to determine the relationship between self-care and personality traits on nurse burnout in the emergency room at Palembang Hospital. This study used a design cross-sectional, a sample of 34 nurses was selected by probability sampling technique with the total sampling method. The instruments used in this research are Burnout Maslach Inventory (MBI), Mini-International Personality Item Pool (M-IPIP), and DSCPI-90. Data analysis used Pearson's test for self-care and burnout variables (r=-0.343; p<0.05), while variables personality traits and burnout used analysis with Spearman rho test for value Extraversion (r = -0.286 ; p> 0, 05), Agreeableness (r = -0.357 ; p < 0.05), Conscientiousness (r = 0.201; p> 0.05), Neuroticism (r = 0.436; p < 0.05), and Imagination (r = 0.328; p> 0.05). The conclusion is the importance of maintaining self-care as a factor that can reduce burnout, and the personality traits of nurses need to be known early so that appropriate action can be taken so that nurses can be protected from burnout.